1996
DOI: 10.1084/jem.183.6.2471
|View full text |Cite
|
Sign up to set email alerts
|

Regulated expression of telomerase activity in human T lymphocyte development and activation.

Abstract: SummaryTelomerase, a ribonucleoprotein that is capable of synthesizing telomeric repeats,.is expressed in germline and malignant cells, and is absent in most normal human somatic cells. The selective expression of telomerase has thus been proposed to be a basis for the immortality of the germline and of malignant cells. In the present study, telomerase activity was analyzed in normal human T lymphocytes. It was found that telomerase is expressed at a high level in thymocyte subpopulations, at an intermediate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
326
1
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(349 citation statements)
references
References 43 publications
19
326
1
3
Order By: Relevance
“…Concommitant upregulation of telomerase with FGF-2-induced NPC proliferation is consistent with the data reported for the hematopoietic system (Engelhardt et al, 1997). Telomerase has been shown to be upregulated in response to cytokine-induced proliferation and cell cycle activation in primitive resting hematopoietic cells that otherwise expressed low or undectable enzymatic activity (Weng et al, 1996), similarly as that we have observed for proliferating NPC. There is strong evidence that FGF2 e ectively modulates telomerase in vivo because telomerase activity is directly correlated to the level of FGF2 expression during brain development.…”
Section: Discussionsupporting
confidence: 83%
“…Concommitant upregulation of telomerase with FGF-2-induced NPC proliferation is consistent with the data reported for the hematopoietic system (Engelhardt et al, 1997). Telomerase has been shown to be upregulated in response to cytokine-induced proliferation and cell cycle activation in primitive resting hematopoietic cells that otherwise expressed low or undectable enzymatic activity (Weng et al, 1996), similarly as that we have observed for proliferating NPC. There is strong evidence that FGF2 e ectively modulates telomerase in vivo because telomerase activity is directly correlated to the level of FGF2 expression during brain development.…”
Section: Discussionsupporting
confidence: 83%
“…As within the group of lymphomas with constantly low telomerase activity (MCL, FL, DLBL) the proliferation varied substantially, a positive correlation of telomerase activity or hTERT expression with proliferation cannot be found. Thus, in contrast to reactive lymphocytes and the GC reaction, telomerase activity and hTERT expression in malignant lymphomas seem to be uncoupled from rates of proliferation (Buchkovich and Greider, 1996;Weng et al, 1996Weng et al, , 1997.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, telomerase activity can be induced in human lymphocytes. 33 Thus, the activation of TERT in chronic hepatitis was thought to reflect an activation of telomerase in infiltrating lymphocytes. 34 Experimental systems to investigate the activation of hTERT in regenerating hepatocytes have been missing.…”
Section: Discussionmentioning
confidence: 99%